P225 The Development Of Evidence Based Guidelines For Opioid Pain Treatment. (15th August 2013) - Effiong, A; Hegmann, K; Thiese, M; Wolfkiel, C; Ording, J; Harris, J; Schwei, K
Abstract : Background: Opioid analgesic-related deaths more than tripled in the US from 1999 through 2006. According to the CDC, 27, 000 unintentional drug overdose deaths occurred in the United States in 2007; the most potent epidemic in the past 100 years. Objectives: To develop opioid guidelines to improve opioid pain treatment and reduce fatalities. Methods: A systematic literature search (including Google Scholar and Medline) was conducted. Randomised controlled trials (RCTs) were categorised into acute, subacute (1–3mo), chronic, and mixed chronicity. The quality of RCTs was determined using previously developed guideline scoring methods; low quality (3.5 or less), moderate quality (4.0–7.5), and high quality (8.0–11.0). Results: A total of 153 RCTs were identified; 11 acute, 2 subacute, 137 chronic, and 3 of mixed chronicity. Of the 11 acute pain RCTs, 1 was low quality, 6 moderate quality, and 4 high quality. Both subacute pain RCTs were moderate quality. Of the 137 chronic pain RCTs, 28 were low quality, 95 moderate quality, and 14 high quality. The RCTs with mixed chronicities were of moderate quality. All trials were under 6 months, with most under 4-weeks duration, precluding statements on long-term safety. Discussion: These opioid guidelines provide more informed recommendations for prescribing opioids for pain treatment with details to be presented. Implications: These guidelines may have considerable implications among prescribing health professionals.